Ovarian Lymphangioma with Mature Cystic Teratoma - Vaidya, Karishma Malla; Shrestha, Bigya (Journal of Nepal Health Research Council, 2019)
Lymphangiomas are slow-growing tumors that remain asymptomatic for a long time, with the tumor being identified incidentally during histopathological examination after excision. Mature cystic teratoma is benign tumor consisting of mature tissue derived from two or three germ layers. We have 47-year-old woman who underwent total abdominal hysterectomy for right adnexal mass. As her ultrasound report revealed a right adnexal mass with solid and cystic components. The histological analysis along with immunohistochemistry (D2-40) maker confirmed the diagnosis of lymphangioma of the ovary coexisting with mature cystic teratoma. There is paucity of reported case of co-existing these two tumors in same tissue.Keywords: D2-40; lymphangioma; mature cystic teratoma; ovary.